Dual color triads: synthesis, photophysics and applications in live cell imaging. (19th May 2021) - Tanrıverdi Eçik, Esra; Özcan, Emrah; Kazan, Hasan Hüseyin; Erol, Ismail; Şenkuytu, Elif; Çoşut, Bünyemin
Abstract : Fluorescent labels and probes constitute an important class of organic materials used in the development of sensor systems and imaging platforms for various chemical and molecular biology applications. Abstract : Fluorescent labels and probes constitute an important class of organic materials used in the development of sensor systems and imaging platforms for various chemical and molecular biology applications. In the development of fluorescent labels and probes, multichromic environment-sensitive fluorophores are very important. In this work, novel triad systems, including subphthalocyanine, BODIPY and thiophene/thianaphthene units, were prepared and their molecular structures were identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and 1 H and 13 C NMR spectroscopy. The optical properties of the subphthalocyanine–BODIPY–thiophene/thianaphthene triads were determined using UV-vis absorption and fluorescence (2D and 3D) spectroscopic methods and quantum chemical calculations. The data were analyzed by comparing the results of the final properties to those of the BODIPY- and subphthalocyanine-alone units. The compounds were also evaluated in live cell imaging using a breast cancer cell line. The novel subphthalocyanine–BODIPY–thiophene/thianaphthene triads displayed dual color emission, which is critically important for the development of novel systems particularly in biomedical applications such as bioimaging and cellular sensor systems.